Plan de mejoramineto integral para la empresa Kobac, dedicada a la comercialización de productos para campañas promocionales en el mercado corporativo de la ciudad de Quito - Salazar Bermeo, Johanna Natalia (2015)
This study will determine the need to implement processes and procedures to achieve a overall improvement for the company KOBAC. KOBAC is an Ecuadorian company dedicated to the marketing of consumer technology for the business market in Quito. This study is divided into four stages. First, the definition of the problem, theoretical framework, diagnosis of the Company and the proposed changes to improve processes. In the first chapter the existing problem is analyzed and determined. This problem is found to be the main reason for the lack of growth expected in KOBAC. Also the structure of the company is analyzed. In the second and third chapter all the information obtained through the first stage is analyzed and frameworks, best practices, papers and concepts of several authors are compiled to discover a number of improvement possibilities for the company. These improvement possibilities are analyzed considering their impact on the processes and their importance. The forth and last chapter contains a proposal focusing on the critical and most problematic processes of the company and in ways to improve them and make them more efficient.